Choosing schools, choosing selves: exploring the influence of parental identity and biography on the school choice process in Delhi, India. Issue 1 (2nd January 2017) - Gurney, Eleanor
Abstract: Drawing on qualitative interview data from a group of lower income parents in Delhi, India, this paper focuses on the dynamic relationship between parental choice of a particular school and parents' own identity construction. The data indicate that choice of school is for some parents a symbolic expression of identity, influenced by family dynamics and parents' educational biographies. The paper outlines the concept of 'forging solidarities' and proposes it as an alternative way of understanding school enrolment decisions that recognises the social significance of such choices for the wider family unit. More generally, as school choice mechanisms in various forms become an increasingly important part of the educational landscape in many countries, the findings draw attention to the sociocultural nature of choice in real-world market settings and the contribution of schooling choices to processes of social and educational segregation.